The Phytochemistry of Selected Ancistrocladus and Monsonia Species and their Anti-Pancreatic Cancer and Nrf2 Activator Properties - Maharaj, Vinesh J. (University of Pretoria, 2020)
Thesis PhD (Chemistry))--University of Pretoria, 2019.